Prospecção fitoquímica e caracterização dos compostos bioativos de Inga laurina (Sw.) Willd (Fabaceae) - Martins, Carla de Moura (2017)
The plant Inga laurina is found in Brazilian cerrado and there are few studies in the literature about this species, so the objective of this work was to identify the chemical constituents of bark and leaves that are responsible for the biological activities observed. Antioxidant activity, antifungal, a-amylase inhibitor, antibacterial and antiprotozoal activity were analyzed. The results showed that the extracts and fractions of the leaves have a great amount of phenolic compounds, especially from the ethyl acetate fraction of leaves (FAE-F), which presented high total phenol content and flavonoids, a result that can explain the antioxidant activity evaluated by the method of DPPH (2,2-diphenyl-1-pictytoy^^yl) radical, the a-amylase enzyme inhibition and the antifungal activity for Candida glabrata. From this fraction, the flavonoid myricetin-3- O-rhamnoside was isolated and eleven phenolic compounds were identified by mass spectrometry (MS): gallic acid, (epi)-gallocatechin, methyl gallic acid derivative, ethyl gallate, myricetin-O-(O-galloyl)-hexoside, myricetin-3-O-galactoside, myricetin galloyl rhamnoside, myricetin, quercetin-3-O-rhamnoside, quercetin-3-O-(2"-galloyl)- rhamnoside and quercetin. After column fractionation of FAE-F, myricetin-3-O-acetyl- rhamnoside, digalloylquinic acid, myricetin-3-O-rhamnose-3'-O-rhamnose, trigalloylquinic acid and vanillic acid, were identified by MS. Extracts and fractions of the bark also showed a high content of phenolic compounds, such as total phenols and proanthocyanidins, especially the ethyl acetate, n-butanol and methanol fractions, which were the most active samples for inhibition of the a-amylase enzyme, antioxidant activity and antifungal activity for the Candida species tested. From the ethyl acetate fraction of the bark (FAEI-C and FAEII-C) were isolated unreported flavonoids and proanthocyanidins in the genus Inga such as 4'-O-methylgallocatechin, gallocatechin, gallocatechin-(4a-8)-4'-O-methylgalocatechin, epigallocatechin-(2—>O—>7,4—>8)-4'-O- methylgallocatechin and epigallocatechin-3-O-galoyl- (2—>O—>7,4—>8)-4'-O- methylgallocatechin. In addition, the compounds epigallocatechin-3-O-gallate, epicatechin-3-O-gallate, 4'-O-methyl-epigallocatechin-3-O-gallate, epigallocatechin-3- O-(3",4"-O-dimethyl) gallate, p-cumaric acid and prodelphinidine B-4 were identified by MS. Therefore, the I. laurina plant was characterized as a promising species as a source of biologically active phenolic compounds.